Ekonomi dan Diversifikasi Media Massa - Lase, Formas Juitan; Rio, Adde Oriza (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2014)
This research tried to reveal how the process of diversification of mass media in Indonesia, particularly the print media to electronic media and digital were influenced by the power of the capital. Logically, mass media must expand to be able in media market. Because the media run by business logic, the media must be eager to have a lot of media units through diversification strategies, to create capital accumulation. By using the political economy theory, this study attempts to examine why the Media Group uses diversification and how the diversification process was carried out. The results showed that the Media Group did the diversify as a logical consequence of economic determinism to reap the benefits of advertising in the new media market opportunities, the consequences of media ownership that makes the media as a political instrument, and the consequences of the technological revolution that creates market opportunities for the segmented audience .